The Determinants of FDI Inflows into the GCC Countries 1990 - 2013 - Khalifah, Khaled (2014)
Over the past several decades the rapid growth in the rate of globalisation has resulted in a marked increase in foreign direct investment (FDI) flows around the world. Foreign direct investment is increasingly seen as a sustainable method of improving as well as maintaining economic growth and contributes to the overall diversification of revenue sources. This especially holds true for emerging economies which are increasingly the main targets of FDI flows around the world, resulting in a healthy competition by a significant amount of countries for a limited amount of investment.